Career Decision Making in the Shadow of Economic Downturn: A Study of Cape Breton High School Students - Chisholm, Joe; Edmunds, Alan (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examined differences in levels of career decision-making self-efficacy in Cape Breton high school students who lived in communities with recent closures of mining and steel industries compared to students who lived in communities with no such plant closures. Students demonstrated considerable confidence in their career decision-making abilities implying that substantive economic downturns may create an urgency that spurs career decision making. However, all students without definite career plans scored significantly lower on career decision-making self-efficacy and may be considered at-risk, suggesting that more specific interventions to improve career decision making are required.